NETWORKS ROLE IN CONTEMPORARY SOCIAL MOVEMENTS AN EMPIRICAL ANALYSIS OF THE ANTINUCLEAR MOVEMENT OF JAPAN - Soliman, Rosemary (European Scientific Journal, ESJ, 2015)
Some scholars tend to limit the role of networks as an instrument that gathers participants in one place to achieve a mutual goal. There is no doubt that networks are mobilized as an instrument in the process of individual participation of a social movement. For example, interpersonal relations and social ties can be categorized as an instrumental network. Instrumental networks played a marginalized role in most of both old and contemporary social movements; the Velvet revolutions in Eastern Europe in 1980s, Japanese student’s strikes in 1970s, and recently the Arab revolutions in 2011. However, interpersonal relations and social ties are not always mobilized for positive purposes like those mentioned above, but they can also be mobilized for negative and radical purposes like what we are witnessing in the Islamic State, Al Qaeda, and other terroristic groups. Many theorists have emphasized on the role of the Interpersonal or instrumental networks in individual participation, and this role is not only found in contemporary social movements, but also in other historical contexts (Shiohara 1988; Oberschall 1973; kriesi 1993; McAdam 1982). The aim of this paper is not to reemphasize on the role of interpersonal networks; rather it is to address other functions that networks have in contemporary social movements that exceeds the role of being just an instrument. By analyzing the Japanese antinuclear movement that took place in Japan after the great Tohoku Earthquake in 2011, I will try to prove my hypothesis that networks have multiple functions and play a great role in collective actions.